2020
DOI: 10.1101/2020.04.14.031971
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Visual attention modulates the integration of goal-relevant evidence and not value

Abstract: AbstractWhen choosing between options, such as food items presented in plain view, people tend to choose the option they spend longer looking at. The prevailing interpretation is that visual attention increases value. However, in previous studies, ‘value’ was coupled to a behavioural goal, since subjects had to choose the item they preferred. This makes it impossible to discern if visual attention has an effect on value, or, instead, if attention modulates the information most … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 45 publications
7
51
0
Order By: Relevance
“…Under this explanation, there would indeed be a causal link between gaze and information processing, but in the opposite direction from that proposed by the above authors. Those authors model gaze shifts as random events (Sepulveda et al, 2020;Krajbich and Rangel, 2011;Krajbich et al, 2010). Our proposal that gaze shifts are driven away from scant information sources and towards rich information sources seems more parsimonious.…”
Section: Replication Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…Under this explanation, there would indeed be a causal link between gaze and information processing, but in the opposite direction from that proposed by the above authors. Those authors model gaze shifts as random events (Sepulveda et al, 2020;Krajbich and Rangel, 2011;Krajbich et al, 2010). Our proposal that gaze shifts are driven away from scant information sources and towards rich information sources seems more parsimonious.…”
Section: Replication Resultsmentioning
confidence: 79%
“…Specifically, it has been proposed that during choice deliberation, evidence accumulates at a higher rate for the option that is currently being gazed at, relative to the other option(s). This evidence might support value estimation directly (Krajbich and Rangel, 2011;Krajbich et al, 2010) or a more general goal-relevant information estimation (Sepulveda et al, 2020). However, neither of these models include value estimate certainty.…”
Section: Replication Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…Specifically, it has been proposed that during choice deliberation, evidence accumulates at a higher rate for the option that is currently being gazed at, relative to the other option(s). This evidence might support value estimation directly (Krajbich et al, 2010;Krajbich and Rangel, 2011) or a more general goal-relevant information estimation (Sepulveda et al, 2020). However, neither of these models include value estimate certainty.…”
Section: Discussionmentioning
confidence: 83%
“…Other recent work has suggested that the evidence accumulation process illustrated by a DDM is influenced by attention (Krajbich et al, 2010;Krajbich and Rangel, 2011;Sepulveda et al, 2020). Specifically, it has been proposed that during choice deliberation, evidence accumulates at a higher rate for the option that is currently being gazed at, relative to the other option(s).…”
Section: Discussionmentioning
confidence: 99%